2023
DOI: 10.3390/diseases11030089
|View full text |Cite
|
Sign up to set email alerts
|

WNT-β Catenin Signaling as a Potential Therapeutic Target for Neurodegenerative Diseases: Current Status and Future Perspective

Abstract: Wnt/β-catenin (WβC) signaling pathway is an important signaling pathway for the maintenance of cellular homeostasis from the embryonic developmental stages to adulthood. The canonical pathway of WβC signaling is essential for neurogenesis, cell proliferation, and neurogenesis, whereas the noncanonical pathway (WNT/Ca2+ and WNT/PCP) is responsible for cell polarity, calcium maintenance, and cell migration. Abnormal regulation of WβC signaling is involved in the pathogenesis of several neurodegenerative diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 262 publications
1
12
0
Order By: Relevance
“…As previously reported, [35][36][37] sporadic PD accounts for approximately 85%-95% of all PD cases. It may result from a complex interplay of genetic susceptibility, environmental factors, age-related changes, oxidative stress, mitochondrial dysfunction, protein misfolding and aggregation, and neuroinflammation.…”
Section: Discussionsupporting
confidence: 63%
“…As previously reported, [35][36][37] sporadic PD accounts for approximately 85%-95% of all PD cases. It may result from a complex interplay of genetic susceptibility, environmental factors, age-related changes, oxidative stress, mitochondrial dysfunction, protein misfolding and aggregation, and neuroinflammation.…”
Section: Discussionsupporting
confidence: 63%
“…3 Current treatment strategies for PD only provide symptomatic relief to patients, with limited effects on modifying the disease course. 4,5 Therefore, searching for neuroprotective agents for preventing neuronal loss in PD is necessary and urgent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…According to the Global Burden of Disease Study (GBD), the prevalence of PD is increasing in the first place among the disabling neurological diseases, leading to an incremental demand for PD diagnosis, treatment, and rehabilitation . Current treatment strategies for PD only provide symptomatic relief to patients, with limited effects on modifying the disease course. , Therefore, searching for neuroprotective agents for preventing neuronal loss in PD is necessary and urgent.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is not any neuroprotective therapy available, although significant development has been made in the treatment of symptomatic PD, since the discovery of L-dopa in the middle of the 20th century (1960s). 10 Therefore, it is of great importance to seek effective drugs with high BBB permeability for delaying the onset or for forestalling the progression of PD.…”
Section: ■ Introductionmentioning
confidence: 99%
“…DAT and VMAT2 are important reference indexes for exploring the pathogenesis of PD, which is supported by that the reduced expression levels of DAT and VMAT2 are obtained in the nigrostriatal pathway of PD patients. , Previous studies have reported that 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) administration to mice results in a severe loss of dopaminergic neurons and a dramatic reduction in striatal DA levels, which is similar to those in PD patients. , The expression levels of DAT and VMAT2 are also decreased in vivo and in vitro models of MPTP/MPP + injury. , Based on the depletion of dopamine in the striatum, most of the current drugs focus on clinical symptom relief to improve the quality of life in PD patients. However, there is not any neuroprotective therapy available, although significant development has been made in the treatment of symptomatic PD, since the discovery of l -dopa in the middle of the 20th century (1960s) . Therefore, it is of great importance to seek effective drugs with high BBB permeability for delaying the onset or for forestalling the progression of PD.…”
Section: Introductionmentioning
confidence: 99%